Evaluasi Dampak Kebijakan Zonasi Sekolah terhadap Kualitas Input Peserta Didik dan Persebaran Siswa di Sekolah Menengah Pertama di Kabupaten Lombok Tengah - Padrian, Muh. (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
Central Lombok Regency for the 2024/2025 academic year and examine its implications for educational justice from an Islamic perspective. The zoning policy serves as an instrument for equalizing access to education and reducing segregation between favored and non-favored schools, although its implementation still faces challenges such as unequal facilities in peripheral schools, uneven teacher distribution, and diverse public perceptions of school quality. Using a descriptive qualitative approach through interviews, PPDB documentation, and a survey of 100 seventh-grade students, the study finds that zoning has encouraged a more equitable distribution of students, increased the heterogeneity of student input, and reduced economic and geographical barriers for families. However, the strong belief in “elite schools” still influences community acceptance. From an Islamic educational perspective, the zoning policy aligns with the principles of ?adl (justice), musawah (equality), and maslahah (public benefit), emphasizing that access to education must be inclusive and nondiscriminatory. The findings highlight that the success of the zoning policy depends not only on regulation but also on improving facilities, equalizing teacher distribution, strengthening school capacity, and enhancing policy socialization to achieve sustainable educational equity.